1996
DOI: 10.1128/iai.64.1.253-261.1996
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant baculovirus 42-kilodalton C-terminal fragment of Plasmodium falciparum merozoite surface protein 1 protects Aotus monkeys against malaria

Abstract: The immunogenicity and protective efficacy of a baculovirus recombinant polypeptide based on the Plasmodium falciparum merozoite surface protein 1 (MSP-1) has been evaluated in Aotus lemurinus griseimembra monkeys. The MSP-1-based polypeptide, BVp42, corresponds to the 42-kDa C-terminal processing fragment of the precursor molecule. Immunization of Aotus monkeys with BVp42 in complete Freund's adjuvant resulted in high antibody titers against the immunogen as well as parasite MSP-1. Fine specificity studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…All immunized monkeys produced significant levels of parasite growth inhibitory antibodies, ranging from 55 to 100% inhibition ( Table 2). This level of inhibition is comparable to studies where Aotus monkeys were vaccinated and protected with MSP1-42-CFA (33). Due to the old age of these monkeys, they were not challenged with blood-stage parasites.…”
Section: Immunogenicity Of Rmsp1-io Nanoparticles In Aotus Monkeyssupporting
confidence: 78%
See 4 more Smart Citations
“…All immunized monkeys produced significant levels of parasite growth inhibitory antibodies, ranging from 55 to 100% inhibition ( Table 2). This level of inhibition is comparable to studies where Aotus monkeys were vaccinated and protected with MSP1-42-CFA (33). Due to the old age of these monkeys, they were not challenged with blood-stage parasites.…”
Section: Immunogenicity Of Rmsp1-io Nanoparticles In Aotus Monkeyssupporting
confidence: 78%
“…It is possible that rMSP1 delivered via IO nanoparticles induced antibodies that are much more focused toward parasite inhibitory epitopes than antibodies induced by rMSP1-CFA or rMSP1-ISA51, which was reflected in the differences in the degree of in vitro parasite inhibition observed (Table 1). More important, our results showed that in the nonhuman primates, the levels of parasite inhibitory antibodies induced by rMSP1-IO were not only significant (55-100% inhibition) but surpassed or matched those levels previously achieved in MSP1-42-vaccinated and protected monkeys (33).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations